Social change in the Age of Enlightenment Edinburgh, 1660 - 1760 - Houston, Robert Allan 1954- (Clarendon Press, 1994)
It is a major contribution not only to Scottish but also to British history
Keywords: Geschichte 1700-1800; Geschichte 1600-1700; Geschichte 1660-1760; Cambio social - Escocia - Edinburgo; Ilustración - Escocia - Edinburgo; Schotse School; Sociale verandering; Stadscultuur; Sozialer Wandel; Enlightenment -- Scotland -- Edinburgh; Social change -- Scotland -- Edinburgh; Aufklärung; Schottland; Edinburgh (Scotland -- Intellectual life -- 17th century; Edinburgh (Scotland -- Intellectual life -- 18th century; Edinburgh (Scotland) -- Social conditions; Edinburgh